EXPERIENCE OF APPLICATION OF THE COMMON TRANSIT PROCEDURE ON THE EXAMPLE OF LATVIA (Development Service Industry Management, 2023)
The article is devoted to the study of international experience in the implementation of joint transit. The purpose of the article is to study the main aspects of the international experience of applying the common transit procedure.To achieve the goal, the following methods were used: induction and deduction, theoretical generalization, abstraction, dialectical cognition - when studying scientific sources and researching theoretical aspects of the implementation of the common transit procedure, determining the categorical apparatus of the investigated issues; abstract-logical – for summarizing theoretical propositions, forming conclusions and proposals on the topic of research. The article analyzes the process of transit system development in the EU. The main aspects of the regulatory and legal regulation of the implementation of the customs procedure of common transit are outlined. The experience of joint transit implementation was analyzed using the examples of Latvia.The advantages of country joining the Convention on the common transit procedure are given, as well as the conditions for applying the common transit procedure are outlined. The peculiarities of the implementation of the common transit procedure in the country under study are analyzed. The essence, content and functionality of the electronic transit system (NCTS), which each of the countries implemented in practical activity, is revealed. The features of the exchange of customs information provided by the NCTS and the security aspects of its preservation within the system are analyzed. The specifics of joint transit and the functional burden on each of the participants in such customs legal relations have been determined. Special attention is paid to the analysis of qualitative changes in the service component of customs activity, achieved as a result of the application of NCTS.
Keywords: transit; common transit; Conventions on common transit procedure; NCTS